LEMBAGA SWADAYA MASYARAKAT (LSM) SEBAGAI KEKUATAN POLITIK - Al-Ra’zie, Zakaria Habib (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Non-Governmental Organizations (NGOs) are non-governmental organizations that fall into the category of political power because they are in direct contact with government policies which are in the political realm. Among the interests of NGOs is that government policies have a widespread impact on society. The presence of NGOs in a modern and democratic political system cannot be avoided, because their presence is needed as mediators or channelers of people's aspirations to the government. However, NGOs can be divided into 3 groups based on their activities and the real interests they are fighting for. This research maps the types of NGOs based on an analysis of the practices carried out by NGOs. This research uses a qualitative method of literature study which is descriptive analysis. The research results found that the practices carried out by a number of NGOs show a shift in the meaning that NGOs do not always fight for the public interest, but can be used to advance personal and group interests.Keywords: Institution; Self-Help; Public; strength; Political.